Opportunities and potential for Community Rangeland Health Workers in Kenya and Somalia - Lutta, Alphayo (International Livestock Research Institute, 2024)
This report presents an assessment of the potential for establishing Community Rangeland Health Workers (CRHWs) in Kenya and Somalia. The study explores the role CRHWs can play in improving rangeland management, enhancing the livelihoods of pastoralist communities, and promoting ecosystem resilience through a One Health framework that links human, animal, and environmental health. The assessment combines insights from literature review and key informant interviews to identify the opportunities, challenges, and strategies for CRHW implementation.